Characteristics of the difference and change in the comprehensive physical properties of rocks - Yu, Ping; Feng, Yong-ge; Zhao, Hong-Ru (Acta seismologica sinica, 2001)
Based on the relationship between rock physical properties and atomic structures of chemical elements, this paper dissertates the characteristics between the difference and change in the comprehensive physical properties of rocks, such as density, elasticity, electrical property and radioactivity,etc. The examples in this paper show that the change of the comprehensive physical parameters of rocks reflects the change of atoms, molecules, minerals and their constitutions in rocks, and there are some correlations between these parameters.